Thermodynamic data of belite polymorphs. (February 2022) - Grevel, K.-D.; Bellmann, F.; Majzlan, J.; Dachs, E.; Benisek, A.; Ludwig, H.-M.
Abstract: One major component of Portland cement clinker is Ca2 SiO4 (C2 S, belite). Synthetic samples of three polymorphs, β-C2 S (larnite), γ-C2 S (calcio olivine), and x-C2 S were investigated by high-temperature oxide melt solution calorimetry at 700 °C to obtain their enthalpies of formation. A natural sample of wollastonite (CaSiO3 ) was measured for comparison. Low-temperature heat capacity data of the C2 S phases were recorded by relaxation calorimetry using a PPMS. Supplementary DSC data of β- and γ-C2 S were obtained to verify their heat capacity evolution to 400 °C. The recommended values for β-C2 S and γ-C2 S are: Δ f H 0 298 γ − C 2 S  = −2316.0 ± 4.5 kJ mol −1, S 0 298 γ − C 2 S  = 119.7 ± 0.9 J mol −1  K −1, C P (γ-C2 S) = (249.098 − 1949.5  T –0.5  – 1.60822 ∙ 10 6   T −2  + 2.77532 ∙ 10 8   T −3 ) J K −1  mol −1, [ T ] = K, Δ f H 0 298 β − C 2 S  = −2307.6 ± 4.5 kJ mol −1, S 0 298 β − C 2 S  = 122.2 ± 0.9 J mol −1  K −1, and C P (β-C2 S) = (259.721 − 2466.09  T –0.5  + 2.62687 ∙ 10 6   T −2  – 4.77891 ∙ 10 8   T −3 ) J K −1  mol −1, [ T ] = K.